Medición y reglas de los mercados mundiales de contratación pública - Zapatero Miguel, Pablo; Petz, Marc (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
The revised Government Procurement Agreement (GPA) illustrates the long-term transformation in the way governments currently deliver public policies: steering, not rowing. Under a regulatory paradigm based on improving efficiency and best value for money, the 51 GPA Parties have reformed the previous GPA framework and expanded global procurement markets in accordance. However, the figures of this structural policy trend have not yet been properly mapped. This research estimates on basis of the available data that the GPA parties cover round 26% (US$2,140bn) of their GGCE (US$8,220bn), whereby the global GPA coverage could potentially be expanded substantially (compare to global GGCE: US$13,100bn) on the long term.
Keywords: partenariados público-privados; comercio mundial; formación de mercados; contratación pública; GPA